Ameliorative effects and mechanism of Panax notoginseng extract on ulcerative colitis mice based on a multi-omics strategy - Song, Yan; Lin, Rui; Fu, Yifeng; Wang, Anna; Yang, Hu; Liu, Wentian (Frontiers in Immunology, 2025)
IntroductionAs a complex and persistent inflammatory bowel disease, the onset and progression of ulcerative colitis (UC) are closely associated with intestinal microbiota dysbiosis, host metabolic imbalance, and impaired intestinal barrier function. The traditional Chinese medicine Panax notoginseng (Sanqi) possesses multiple therapeutic properties, among which its anti-inflammatory effect is particularly remarkable. However, the specific molecular pathways through which Panax notoginseng exerts its anti-UC effects have not been fully elucidated. This study aims to clarify the efficacy and molecular mechanisms of Panax notoginseng extract in a mouse model of UC.MethodsA colitis model was established by inducing UC in ICR mice using dextran sulfate sodium (DSS). The experimental animals were divided into four groups: normal control group (CON), normal administration group (CONSQ), DSS-induced model group (DSS), and DSS-induced administration group (DSSSQ). The CONSQ and DSSSQ groups received oral gavage of 200 mg/kg Panax notoginseng extract. The evaluation indicators included the disease activity index, histopathological examination of colon tissue, expression of key intestinal barrier proteins, analysis of intestinal microbiota structure, and metabolomic testing of fecal samples.ResultsTreatment with Panax notoginseng extract repaired the damaged intestinal barrier, as evidenced by increased expression levels of Claudin-1, Occludin, ZO-1, and MUC-2 proteins. Simultaneously, the extract favorably modulated the structure of the intestinal microbiota, specifically by increasing the Firmicutes/Bacteroidetes ratio and enriching probiotic genera (such as Bifidobacterium and Lactobacillus). Furthermore, the extract significantly reduced the levels of characteristic metabolites (such as LysoPI and Etamiphylline). Correlation analysis based on multi-omics data revealed an interactive regulatory network centered on the intestinal microbiota, host metabolites, and intestinal barrier integrity, indicating that Panax notoginseng extract alleviates the pathological process of UC through a multi-target, synergistic approach.DiscussionThe results of this study demonstrate that Panax notoginseng extract exerts its therapeutic effects on UC by repairing the intestinal barrier, modulating the composition of the intestinal microbiota, and influencing the host metabolic profile. Multi-omics correlation analysis further revealed the central role of the microbiota–metabolite–barrier axis in the anti-UC effects of Panax notoginseng, providing strong evidence for its multi-target synergistic mechanism. These findings lay the foundation for a deeper understanding of the pharmacological mechanisms of Panax notoginseng in UC treatment and support its further development as a potential therapeutic agent for UC.